Livin' la Vida Barroca American Culture in an Age of Imperial Orthodoxies - Harrington, Thomas S. (Biblioteca Javier Coy d'estudis Nord-Americans, 2014)
Thomas S. Harrington is a professor of Hispanic Studies at Trinity College in Hartford, Connecticut where he teaches courses on 20th and 21st Century Spanish Cultural History, Literature and Film. His areas of research expertise include modern Iberian nationalist movements. Contemporary Catalonia, cultural theory, the epistemologies of Hispanic Studies and the history of migration between the peninsular «periphery» (Catalonia, Galicia, Portugal and the Basque Country) and the societies of the Caribbean and the Southern Cone. In recent years, he has begun, in essays such as those contained in the present volume, to apply the insights gained in the course of his work on the formation of Iberian social identities to the task of unpacking the cultural architecture of nationalist and imperialist discourses in the land of his birth.@Thomas S. Harrington es catedrático de Filología Hispánica en el Trinity College de Hartford (Connecticut), donde imparte cursos sobre la historia cultural española de los siglos XX y XXI. Sus áreas de investigación incluyen los movimientos nacionalistas ibéricos modernos como la Cataluña contemporánea, la teoría cultural, las epistemologías de los estudios hispánicos y la historia de la migración entre la «periferia» peninsular (Cataluña, Galicia, Portugal y el País Vasco) y las sociedades del Caribe y del Cono Sur. En los últimos años ha comenzado a aplicar, en ensayos como los que se presentan en este volumen, los conocimientos adquiridos en el trascurso de su trabajo de formación de las identidades sociales ibéricas con el objetivo de desembalar la arquitectura cultural de los discursos nacionalistas e imperialistas de su tierra natal.